Paleoredox Conditions of Paleocene to Miocene Rocks of Eastern Benin (Dahomey) Basin, Nigeria: Implications for Chemostratigraphy - I. O, Adelabu; S. A, Opeloye; O. A, Oluwajana; O.A, Ogbahon (International Journal of Geography and Geology, 2021)
The major oxides and trace elements, of two wells spanning the Paleocene – Miocene of the Benin Basin, were used to infer the varying paleoredox conditions during deposition of the different rock units and identify the chemostratigraphic boundaries. The major oxides revealed four boundaries in these wells, while trace elements suggest five and three chemostratigraphic boundaries for BH and AJ wells respectively. The information from V/Sc, Ni/V and V/(V+Ni) ratios indicates the prevalence of oxic conditions in the sandy upper 25m of the BH well and the interval between 1046 – 1485m of the AJ well. The redox sensitive trace elements of the shaly middle parts of the BH well suggest dysoxic – anoxic conditions and in most parts of the AJ well.